2021
DOI: 10.33062/mjb.v6i1.431
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Work-Life Balance with Work Motivation as Mediating Factor on Job Satisfaction A Prediction toward Transition to New Normal Situation

Abstract: This study aimed to examine the effect of work-life balance and work motivation on job satisfaction. The literature review used to discuss the dynamics between variables is work-life balance, motivation and job satisfaction. The approach to this research is quantitative, and the number of respondents involved in this study was 212 people who filled out the survey through an online survey. We collect data during new normal situations. The data analysis technique in this study refers to the structural equation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…Another research that supports this finding is research on textile companies in Indonesia (Tannady & Gunawan, 2020), which unveils that work motivation has a positive and significant effect on employee engagement. This study is supporting previous studies by Alfatihah, Nugroho, Haessel, &Maharani (2021) andSuhartono (2015). Alfatihah et al (2021) concluded that motivation has a significant influence on job satisfaction after studying 200 respondents in Indonesia regarding the changes in their motivation and job satisfaction corresponding to the COVID-19 New Normal protocol.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Another research that supports this finding is research on textile companies in Indonesia (Tannady & Gunawan, 2020), which unveils that work motivation has a positive and significant effect on employee engagement. This study is supporting previous studies by Alfatihah, Nugroho, Haessel, &Maharani (2021) andSuhartono (2015). Alfatihah et al (2021) concluded that motivation has a significant influence on job satisfaction after studying 200 respondents in Indonesia regarding the changes in their motivation and job satisfaction corresponding to the COVID-19 New Normal protocol.…”
Section: Discussionsupporting
confidence: 93%
“…This study is supporting previous studies by Alfatihah, Nugroho, Haessel, &Maharani (2021) andSuhartono (2015). Alfatihah et al (2021) concluded that motivation has a significant influence on job satisfaction after studying 200 respondents in Indonesia regarding the changes in their motivation and job satisfaction corresponding to the COVID-19 New Normal protocol. Suhartono (2015) found a similar result after studying employees in a poultry producer company in Makassar, Indonesia.…”
Section: Discussionsupporting
confidence: 93%
“…The reasons can be explained as the duties of women in the region are not end up when they reach home therefore, the reactions to the interference with work or personal lives are very different with males. JARHE 15,2 Alfatihah et al (2021) reported a strong effect of WLB on work motivation for employees between the age group of 20-25 holding a bachelor's degree and having worked in the tertiary industry. Sukirno (2018) did not find any significant relationship between demographics variables (age, gender, experience and education) and lecturer productivity among university lecturers.…”
Section: Discussionmentioning
confidence: 99%
“…Alfatihah et al. (2021) reported a strong effect of WLB on work motivation for employees between the age group of 20–25 holding a bachelor’s degree and having worked in the tertiary industry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation